RESEARCH ON THE IMPACT OF THE USER EXPERIENCE FOR THE SUCCESS OF A VIRTUAL PRODUCT: BULGARIAN TRAVEL AGENCY WEBSITES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The huge and ubiquitous of the Internet usage, confirms that websites consist a critical competitive resource for tourism business. For the purpose of this report, a study of the user experience of virtual products - websites of Bulgarian travel agencies were prepared. Nine of most of popular Bulgarian sites were selected, namely: "Alexander Tour", "Bohemia", "Ecuador", "Emerald", "Globus", "Mistral", "Red Tours", "RuAl" and "Sun Travel". Data collection was performed through an electronic questionnaire, which was based on Google Forms. The results obtained showed that among all the quality factors, ease of understanding, response time and intuitive functioning of the website (ease of use and navigation) were the most important. The study was tested on a sample of 95 customers of travel websites targeting the Bulgarian market. In conclusion, a positive correlation was found between the overall perceived quality and purchase intentions.